Pengaruh Terpaan Konten TikTok sebagai Media Komunikasi Pemasaran terhadap Minat Beli pada Kedai Nongs (Survei terhadap Followers Akun @jelitawidiaw) - Rifkah Fauziah; Hardiyanti, Rini; Abdurrahman, Ade Irfan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to determine the effect of exposure to TikTok content as a marketing communication medium on purchasing interest at Kedai Nongs. This research uses quantitative research methods with a positivism paradigm, where data is obtained through questionnaires distributed to 100 @jelitawidiaw followers. Sampling was carried out using the Slovin formula. The results of the research show that variable Apart from that, the results of the coefficient of determination test (R2) show that Exposure to TikTok Content has an influence of 26.5% on Purchase Interest at Kedai Nongs. Thus, it can be concluded that exposure to @jelitawidiaw's TikTok content has a significant influence on purchasing interest in Kedai Nongs. So these findings emphasize the importance of using social media, especially TikTok, as an effective marketing communication tool in increasing purchasing interest.